2022
DOI: 10.1001/jamaneurol.2022.1520
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Temporal Trends in Stroke Incidence in Younger vs Older People

Abstract: ImportanceOverall stroke incidence is falling in high-income countries, but data on time trends in incidence of young stroke (ie, stroke in individuals younger than 55 years) are conflicting. An age-specific divergence in incidence, with less favorable trends at younger vs older ages, might be a more consistent underlying finding across studies.ObjectiveTo compare temporal trends in incidence of stroke at younger vs older ages in high-income countries.Data SourcesPubMed and EMBASE were searched from inception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 92 publications
4
43
0
Order By: Relevance
“…This finding of an absolute increase in incidence of young stroke validated UK hospital admission trends and was consistent with findings in the US . The relative divergence in incidence in younger vs older patients was also consistent with a linked systematic review in which analysis of all stroke incidence studies in the 21st century in high-income countries revealed less favorable trends in stroke incidence at younger ages vs older ages …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding of an absolute increase in incidence of young stroke validated UK hospital admission trends and was consistent with findings in the US . The relative divergence in incidence in younger vs older patients was also consistent with a linked systematic review in which analysis of all stroke incidence studies in the 21st century in high-income countries revealed less favorable trends in stroke incidence at younger ages vs older ages …”
Section: Discussionsupporting
confidence: 87%
“…Fourth, the current study results are based on a predominantly White population and might not be generalizable to other ethnic groups in whom stroke incidence might be higher . However, a similar magnitude of increase in incidence of young stroke was also found in the other population in this study, and no differences between ethnic groups were seen in the linked systematic review . Fifth, the diagnosis and management of acute myocardial infarction have changed over the last 20 years, including more sensitive assays for troponin over time and the introduction of primary percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The strengths of this systematic review include the availability of population-based studies, most of which met the suggested ' standard or advanced criteria for ideal stroke incidence studies ' and covered a long period 1,19 , with age and sex disaggregated data available. However, there are only a limited number of published reports from few countries, so our results should be interpreted with caution due to possible selection bias, the potential for unmeasured confounders, the lack of information on stroke severity/type and prevention strategies; and heterogeneity from the use of different methodology between older studies compared to more recent ones.…”
Section: Discussionmentioning
confidence: 99%
“…Disaggregated data of incidence rate (IR) were extracted from each article by sex and age (men: women, and age groups of <55 vs. ≥55 years and <45 vs. ≥45 years). The cut-off age of 55 was selected because it is the youngest age criterion used in previous epidemiological studies1 . When enough data were available, a cutoff age of 45 years was used, given current concerns regarding stroke in the young.…”
mentioning
confidence: 99%